The effects of a 4-week coffeeberry supplementation on antioxidant status, endurance, and anaerobic performance in college athletes - Ostojic, S. M.; Stojanovic, M. D.; Djordjevic, B.; Jourkesh, M.; Vasiljevic, N. (Research in Sports Medicine, 2008)
The main aim of this investigation was to evaluate the changes in total antioxidant capacity (TAC) and aerobic and anaerobic performance induced by supplementation of coffeeberry (CB) formulation for 4 weeks in college athletes. Twenty college athletes (14 males and 6 females) were allocated to two randomly assigned trials. Subjects in the CB group orally ingested capsules that contained CB formulation at a dose of 800 mg per day in two equal doses for 28 days, while subjects in the placebo (P) group ingested an equal number of identical-looking caps that contained cellulose. There were no changes in glucose, cholesterol, and lipoproteins within or between trials (p > 0.05). Total antioxidant capacity (TAC) was significantly higher in the CB versus P trial at the post- supplementation trial (1.66 ± 0.16 vs. 1.51 ± 0.05 mmol/L; p < 0.05). There were no statistically significant changes in average anaerobic power, index of anaerobic fatigue, maximal heart rate, blood lactate, and maximal oxygen uptake within or between trials (p > 0.05). Heart rate recovery (HRR) index increased significantly in CB group as compared with baseline level (38 ± 4 vs. 32 ± 5 beats/min; p < 0.05). Blood lactate after 10 min of recovery (Lactrec) significantly decreased in the CB group after supplementation protocol as compared with initial results (7.6 ± 4.2 vs. 5.5 ± 2.6 mmol/L; p < 0.05). No subject reported any side effects from CB or P. The results of the present study indicate that supplementation with a CB formulation slightly increased antioxidant capacity, but there were minimal effects on recovery parameters after exercise in college athletes.